Functional groups of entomofauna associated to aquatic macrophytes in Correntoso river, Rio Negro sub-region, Pantanal, Mato Grosso do Sul State, Brazil - doi: 10.4025/actascibiolsci.v34i1.7822 - Silva, Fábio Henrique; Favero, Silvio; Sabino, José (Acta Scientiarum. Biological Sciences, 2011)
This work aimed to study the structure of functional groups of entomofauna associated to aquatic macrophytes in Correntoso river, Rio Negro sub-region, Pantanal, Mato Grosso do Sul State, Brazil. Six samples were taken in different seasonal periods; ebb, dry and wet. The organisms were collected using D net (300 m mesh), sweeping five times through the roots of macrophyte banks at each sample session. Three environments were compared (open, intermediary, close) using data from six collection sites, through which were analyzed absolute abundance, observed richness of families and the sampled specimens were also separated in functional groups. A total of 60 families from 12 orders of Insecta were registered, totaling 19,773 sampled insects. The largest number of families was categorized into predators functional group, with 34 families collected, followed by the collectors with 17, shredders-herbivores ten and scrapers eight.